2006
DOI: 10.1007/bf02912938
|View full text |Cite
|
Sign up to set email alerts
|

Depleted nitrite and enhanced oxidative stress in urolithiasis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Indirect evidence via monitoring biomarkers such as reactive oxygen species, and reactive nitrogen species production, antioxidant defense indicates oxidative damage may be involved in the pathogenesis of these diseases [23,24] Oxidative stress also contributes to tissue injury following irradiation and hyperoxia, as well as in diabetes and is likely to be involved in age-related development of cancer. Infection by Helicobacter pylori which increases the production of reactive oxygen and nitrogen species in human stomach is also thought to be important in the development of gastric cancer [25]. ROS also have been reported to damage cellular components in cartilage by impairing the chondrocyte responses to growth factors and migrating to the sites of cartilage injury leading to osteoarthritis [26].…”
Section: Some Of the Human Disorders Clinically Linked To Oxidative Smentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect evidence via monitoring biomarkers such as reactive oxygen species, and reactive nitrogen species production, antioxidant defense indicates oxidative damage may be involved in the pathogenesis of these diseases [23,24] Oxidative stress also contributes to tissue injury following irradiation and hyperoxia, as well as in diabetes and is likely to be involved in age-related development of cancer. Infection by Helicobacter pylori which increases the production of reactive oxygen and nitrogen species in human stomach is also thought to be important in the development of gastric cancer [25]. ROS also have been reported to damage cellular components in cartilage by impairing the chondrocyte responses to growth factors and migrating to the sites of cartilage injury leading to osteoarthritis [26].…”
Section: Some Of the Human Disorders Clinically Linked To Oxidative Smentioning
confidence: 99%
“…Increased ROS in human heart is associated with arotic valve stenosis [28]. Excess ROS in human kidney leads to urolithiasis [29]. It was also observed that hyperglycemia triggers the generation of ROS in both mesangial and tubular cells of human kidney, making structural and functional changes in glomeruli causing diabetic nephropathy [30].…”
Section: Some Of the Human Disorders Clinically Linked To Oxidative Smentioning
confidence: 99%
“…However, high concentrations of ROS contribute to the development of various diseases, including kidney stones. Increased prooxidant damage indicators have been observed in the urine of patients with kidney stones [ 34 ]. There are multiple associations between ROS and kidney stone formation, and an imbalance between prooxidants and antioxidants drives kidney stone formation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pro-oxidant and antioxidant imbalance may contribute to the development of kidney stones. Consequently, patients with kidney stones were characterised by increased lipid peroxides, while nitrite and α-tocopherol levels were reduced in the serum [66]. Previous studies proved that patients with nephrolithiasis were characterised by an increased level of pro-oxidative damage markers in urine, including 8-hydroxydeoxyguanosine (8-oxoG, a marker of DNA oxidative damage) and thiobarbituric acid-reactive substances (TBARS, a marker of lipid peroxidation) [67].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…On the other hand, surgical removal of the renal calculus may contribute to a decrease in malonyl dialdehyde (MDA, 29%) and an increase in Gpx activity (by 50%), reaching values close to the levels of the control group [74]. Previous studies have suggested that an elevated peroxidation and depletion of thiol level may contribute to an increase in the oxalate binding activity and damage to the renal tubular cells, which in turn promotes nucleation, crystal adherence and aggregation of stones [66]. Therefore, in idiopathic CaOx stone cases, a high urine level of renal enzymes indicative of renal tubular damage was observed, such as γ-glutamyl transpeptidase, angiotensin 1 converting enzyme, β-galactosidase and N-acetyl-beta-Dglucosaminidase (NAG), and products of lipid peroxidation, including MDA.…”
Section: Oxidative Stressmentioning
confidence: 99%